The iCAL4LA: Proposing Design Principles of Navigational and Object Interaction for Low Achieving Children - Ahmad, Siti Zulaiha; Abdul Mutalib, Ariffin (Advanced Science Letters, 2017)
Low achieving children require a helpful and fun learning assistance. As a response to that, this paper discusses an on-going study in proposing an interactive computer assisted learning for low achieving children, which specifically focuses on extracting and proposing design principles. The design principles of navigational design and object interaction design are part of components of the conceptual design model proposed for low achieving children.This study extracted the design principles from the previous studies in the literature, and was justified in user-centered design seminar.As the result, three elements of object interaction design and four elements of navigational design have been proposed. Having proposed the elements, this study presents the principles of each element that specifically caters to fun and helpful learning experience of low achieving children.